Teachers’ psychological readiness to work in conditions of inclusive training and education - Lucia Iglikovna Bekembetova, Irina Yuryevna Mordvintseva, Raushan Bilanovna Ordabaeva,; Elnura Toregeldievna Kurmanalieva, Ainur Sakhovna Berdenova, (Opción, 2020)
The aim of the research is to study the main theoretical and methodological aspects of the inclusive education domestic model introduction problem via comparative qualitative research methods. The results of an empirical study showing the presence of a problem in psychological readiness for educational activities in an inclusive class among the students of a pedagogical university are presented. In conclusion, the theoretical analysis of scientific research and advanced pedagogical experience allows to determine the psychological readiness for professional activity as the most important category for the successful implementation of inclusion principles in a modern school.